Study of adverse drug reaction and causality assessment of antidiabetic drugs - M., Shanthi; C., Madhavrao (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Study about adverse drug reaction of antidiabetic drugs helps in ensuring maximum benefits of drug therapy. Methods: An observational study was carried out in patients attending tertiary care hospital in Kanyakumari district from August 2013 to August 2014. Adverse drug reactions due to the use of antidiabetic drugs were collected and adverse effects experienced by the patient was assessed using WHO scale, Naranjo scale, Schumock and Thornton scale and Hartwig and Siegel scale. Results: In this prospective study a total of 76 adverse events (41 male and 35 female) were identified. Most frequently observed adverse effect were hypoglycaemia and the less observed were pruritis. Maximum of 14 adverse effect were observed due to use of insulin. Combination of sulphonylurea and biguanides caused 28 adverse effects. Assessment of adverse effect using WHO scale showed 64% as probable, 16% possible, 7% conditional, 5% unclassifiable, 4% certain, and 4% unlikely. Relationship of adverse reaction to antidiabetic drugs using Naranjo scale showed 92% possibly, 5% probably and 3% as definite. Antidiabetic drug adverse effects were not preventable in 63%, definitely preventable in 19% and probably preventable in 18% as per modified Schumock and Thornton scale. Severity assessment of adverse effects were mild in 75%, moderate in 25% and no severe reactions according to modified Hartwig and Siegel scale. Conclusions: Adverse effect most commonly encountered during the study period were predictable, definitely preventable and without serious effects. Majority of the reactions were due to combination of antidiabetic drugs.